Rasio Efisiensi Keuangan Daerah dan Keserasian dalam Meningkatkan Pembangunan Daerah Kabupaten Aceh Barat - Yasriza, Yasriza; Wahyuningsih, Yayuk Eko (Medan Resource Center, 2023)
In the analysis of the financial conditions of Aceh Barat Regency, it is revealed that a significant dependency on Central Transfers, particularly through the General Allocation Fund (DAU) and Special Allocation Fund (DAK), creates challenges in achieving stable financial independence. Although Regional Original Income (PAD), such as local taxes and regional levies, contributes, the fluctuations indicate complexity and risks in achieving financial balance. Diversification of income sources becomes a primary focus to address dependence on natural resources and the fisheries sector, as well as external fluctuations. Optimization of local taxes, levies, and tourism sector development emerges as key strategies to strengthen Regional Original Income. Additionally, the analysis of the Regional Financial Efficiency Ratio (REKD) indicates characteristics of inefficiency during the period 2011-2022, indicating the need for improvements in budget management and revenue collection. The Harmony Ratio, depicting an increase in Operational Expenditure and a tendency of decreasing Capital Expenditure, highlights the need to achieve a better balance between long-term investments and operational aspects. Therefore, Aceh Barat Regency needs to take proactive steps to enhance financial efficiency, diversify income, and allocate funds wisely to achieve sustainable and financially stable economic growth.